PERBEDAAN TINGKAT KECEMASAN ANTARA LAKI-LAKI DAN PEREMPUAN YANG AKAN MENJALANI OPERASI ELEKTIF POST PREMEDIKASI DENGAN ALPRAZOLAM - , dr. Rory Denny saputra ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. Nowadays, prevalence of anxiety level experienced by patients prior to surgery is about 60%, which able to cause emotional discomfort and so interfere with surgical procedures. Comparison of anxiety levels between male and female patients was 2:1, in both acute and chronic anxiety. Alprazolam proven to be effective at reducing preoperative anxiety up to 80% with no side effect was found. None evidence about equal effectiveness of alprazolam in reducing anxiety levels between male and female patients. Objective. The present study was conducted to explore the effectiveness of alprazolam in preventing anxiety level in male and female patients who will undergo elective surgery. Methods. Study design was clinical test with the total of 106 patients recruited. Ordinal and nominal data was analyzed using chi-square test, while the interval and ratio data was analyzed using independent t-tests. P value < 0.05 was declared significant with 95% confidence level. Anxiety level score was measured in male and female patients who were given premedication alprazolam. Result. Average score of male patients compared to female patients in the treatment room was 45.75 ± 16.87 compared to 52.48 ± 25.03, whereas in the preparation room was 35.40 ± 18.07 compared to 42.52 ± 22, 13. There was no statistically significant difference of mean anxiety levels score between both in the preparation room (p> 0.05). the result said that the use of alprazolam 0.5 mg can lower anxiety levels in both male and female patients, indicated by results of categorization. Male and female patients who were not anxious when measured in the treatment room was`7 people (13.5%) and 4 people (7.4%), respectively. Anxiety was not found in 18 male patients (34.6%), and 17 female patients (31.5%) measured in preparation room. Conclusion. It can be concluded that alprazolam 0.5 mg premedication was proven to reduce levels of anxiety in both male patients and women who will undergo elective surgery. There was no statistically significant difference in anxiety level between male and female patients who will undergo elective surgery post premedication with alprazolam.